2006
DOI: 10.1007/s00467-006-0106-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of with-no-lysine [K] kinases in the pathogenesis of Gordon’s syndrome

Abstract: Gordon's syndrome, also known as pseudohypoaldosteronism type II (PHA II) or familial hypertension with hyperkalemia, is an autosomal-dominant disease characterized by hypertension, hyperkalemia, hyperchloremic metabolic acidosis, and normal glomerular filtration rate. Recent positional cloning has linked mutations of WNK1 and WNK4 to Gordon's syndrome. With-no-lysine [K] (WNK) kinases are a new family of large serine-threonine protein kinases with an atypical placement of the catalytic lysine. Here, we review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…When loaded on gel, these amplifications revealed an approximately 650-bp band from the brain tissues and an approximately 950-bp band from the DRG (Figure 2E, arrows 3 and 4). The subsequent sequencing of these 2 fragments showed that both the brain and DRG lacked exon 11 (462 bp) and that the brain additionally lacked exon 12 (285 bp) ( Figure 2F); this alternative splicing confirmed previous reports in which exons 11 and 12 were shown to be skipped in some Wnk1 mRNAs expressed in mouse tissues (13,23). Further amplifications of the region between the last exons of Wnk1 and Hsn2 were, however, more difficult because of the large distance between these primers; nonetheless, a product corresponding to the expected mRNA size (3.8 kb) could be amplified from Hsn2 to exon 24 of Wnk1 ( Figure 2E, arrow 1).…”
Section: Compound Heterozygous Mutation In Wnk1 and Hsn2 Cause Hsaniisupporting
confidence: 89%
See 1 more Smart Citation
“…When loaded on gel, these amplifications revealed an approximately 650-bp band from the brain tissues and an approximately 950-bp band from the DRG (Figure 2E, arrows 3 and 4). The subsequent sequencing of these 2 fragments showed that both the brain and DRG lacked exon 11 (462 bp) and that the brain additionally lacked exon 12 (285 bp) ( Figure 2F); this alternative splicing confirmed previous reports in which exons 11 and 12 were shown to be skipped in some Wnk1 mRNAs expressed in mouse tissues (13,23). Further amplifications of the region between the last exons of Wnk1 and Hsn2 were, however, more difficult because of the large distance between these primers; nonetheless, a product corresponding to the expected mRNA size (3.8 kb) could be amplified from Hsn2 to exon 24 of Wnk1 ( Figure 2E, arrow 1).…”
Section: Compound Heterozygous Mutation In Wnk1 and Hsn2 Cause Hsaniisupporting
confidence: 89%
“…PHAII is a dominant disorder, the main feature of which is hypertension (12,13). Members of the WNK family contain a Ser/Thr catalytic domain similar to that of other kinases.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the role of WNK1 in mitosis does not primarily account for the lethality of its deletion. In reconstitution assays, multiple WNK family members can regulate several common effectors not limited to OSR1 and SPAK (1)(2)(3)(4). In this regard, we have been unable to detect other WNKs in HeLa cells by immunoblotting.…”
Section: Discussionmentioning
confidence: 72%
“…cytokinesis | microtubules | serine-| proline-| alanine-rich kinase T he serine/threonine protein kinase WNK1 [with no lysine (K)] is important for blood pressure regulation (1)(2)(3)(4). Positional cloning identified two of the four WNK family members as the genes mutated in a form of hypertension known as pseudohypoaldosteronism type II (5).…”
mentioning
confidence: 99%
“…WNKs are activated by changes in tonicity. Cellular reconstitution studies and mouse genetics demonstrated the importance of WNK function in cell volume regulation and maintenance of blood pressure (13)(14)(15)(16)(17)(18)(19). Control of cation-chloride cotransporters through OSR1 and SPAK is among the best-documented actions of WNKs in diverse tissues (5,(20)(21)(22).…”
mentioning
confidence: 99%